Responsible parenthood in the context of contemporary challenges = La parentalité responsable dans le contexte des défis de l’époque contemporaine = La genitorialità responsabile nel contesto delle sfide della contemporaneità - Swito, Lucjan (Philosophy and canon law, 2016)
The article undertakes the subject matter of responsible parenthood, as a significantissue from the point of view of Catholic teaching. The article systematizes and organizes basic notions concerning responsible parenthood and, first of all, makes the reader acquainted with the most important challenges and threats faced today by Catholic spouses. The source of threats for a responsible parenthood includes not only contraception, abortion, assisted procreation or surrogacy, but also the unchecked inflow of immigrants from Muslim countries into the European Union. Immigrants of Muslim origin represent not only a different system of values and culture, but also a different legal system, which is incompatible with the Western model. In view of the fact that some institutions of Muslim law, for instance kafala, are adopted into the legal systems of the Western Europe states, in the short term perspective we may face the problem of serious demands by Islamic communities, which may collide with the Christian system of values and upbringing and become a threat to responsible parenthood in the dimension of child-rearing. It may result in Christian parents taking care of children of Muslim origin, who will be obliged to bring them up according to guidelines of sharia, and not the Gospel.